PENGARUH KOMPETENSI TERHADAP PRESTASI KERJA KARYAWAN BAGIAN MARKETING PADA KOPERASI SERBA USAHA (KSU) SINAR JAYA MALANG - Arifin, Muhammad Budi (Manajemen Bisnis, 2014)
The purpose of this study was to determine the effect of competence on the part of employes job performance marketing division. This type of research is a quantitative study conducted on 32 employees of the marketing Koperasi Serba Usaha (KSU) Sinar Jaya Malang. Analysis tools used were a range of scales and multiple linear regression analysis. The results of research competence influence on employee performance, including the ability to know that the competence evidenced in the high category with an average score scale range is 100.67, competence knowledge in very high category with a score of 105, and competence in the category of self-concept is also very high with the average score scale range is 109.67. Employee performance in the high category, indicated by an average score of 93.33 scale range.Keywords: The Characteristics of Individuals, Competence and employee performance, Marketing.